Elections and Economic Policy in Developing Countries. - Chauvet, L; Collier, P (Centre for the Study of African Economies, 2008)
This paper investigates whether elections in developing countries have improved economic policies and economic governance. Both casual empiricism and casual theorizing suggest that they have done so. As contested elections have become more common since the 1990s, the policy ratings from the World Bank and the International Country Risk Guide have both improved markedly. These improvements accord with the fundamental notion that elections discipline governments into good performance.